Sustainability of Islamic Rural Banks: A Social Qardh Financing Approach - Hasan Al-Banna; Achmad Nurdany (Global Review of Islamic Economics and Business, 2021)
Unlike Islamic commercial banks, Islamic rural bank emphasizes on small-medium enterprise financing along with providing a unique contract feature, namely social qardh financing. This paper investigates a way of finding the sustainability of Islamic rural banks through social financing and halal small-medium enterprise lending. We use OLS (ordinary least squares) and TSLS (two-stage least square) analysis. The time-series data is used from the period of 2010 to 2020.  The result revealed that social qardh financing and small-medium halal enterprise lending have a positive and significant impact on the sustainability of Islamic rural banks. The Islamic rural banks' ratios are also found to be negative in influencing sustainability except the liquidity ratio that has a significant positive effect. Besides, the macroeconomic variables are also significant in explaining sustainability of Islamic rural banks. Recommendation for the policymaker that the regulation is needed to push Islamic rural banks in enhancing the social qardh financing toward small-medium enterprises.